Ancient and modern scats record broken ecological interactions and a decline in dietary breadth of the critically endangered kākāpō parrot (Strigops habroptilus) - Boast, Alexander P.; Wood, Jamie R.; Bolstridge, Nicola; Perry, George L. W.; Wilmshurst, Janet M. (Frontiers in Ecology and Evolution, 2023)
Threatened animal taxa are often absent from most of their original habitats, meaning their ecological niche cannot be fully captured by contemporary data alone. Although DNA metabarcoding of scats and coprolites (palaeofaeces) can identify the past and present species interactions of their depositors, the usefulness of coprolites in conservation biology is untested as few endangered taxa have known coprolite records. Here, we perform multilocus metabarcoding sequencing and palynological analysis of dietary plants of >100 coprolites (estimated to date from c. 400–1900 A.D.) and > 100 frozen scats (dating c. 1950 A.D. to present) of the critically endangered, flightless, herbivorous kākāpō (Strigops habroptilus), a species that disappeared from its natural range in Aotearoa-New Zealand (NZ) after the 13th C. A.D. We identify 24 orders, 56 families and 67 native plant genera unrecorded in modern kākāpō diets (increases of 69, 108 and 75% respectively). We found that southern beeches (Nothofagaceae), which are important canopy-forming trees and not an important kākāpō food today, dominated kākāpō diets in upland (c. >900 m elevation) habitats. We also found that kākāpō frequently consumed hemiparasitic mistletoes (Loranthaceae) and the holoparasitic wood rose (Dactylanthus taylorii), taxa which are nutrient rich, and now threatened by mammalian herbivory and a paucity of dispersers and pollinators. No single dataset or gene identified all taxa in our dataset, demonstrating the value of multiproxy or multigene datasets in studies of animal diets. Our results highlight how contemporary data may considerably underestimate the full dietary breadth of threatened species and demonstrate the potential value of coprolite analysis in conservation biology.